(3OjhGf GdTTJQjs - (3CHhGdMSf Ydj Hf YHO Gddg GdTTJQj GdfejQj GdaGQSj,J (B668 (3g` s ((3YHOGddg GdefUhQj s)
(3ChdgG (B:s
(3bGd QVj Gddg Yfg(B: (3HOCJ HPcQ GdMHjH hgeoJ hYjTj WqjH hoHMJ HSQ YLjH s
(3BNQgG (B:s
(3bdH UH MGdg Yf ecfS hgh aj MQ hNaj eKd eG dYHJ QjM GdUHG HGdbHS s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B120s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B510 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B132 s
Keywords: (3GdCOHs